2016
DOI: 10.1128/mcb.00173-16
|View full text |Cite
|
Sign up to set email alerts
|

Gata3 Hypomorphic Mutant Mice Rescued with a Yeast Artificial Chromosome Transgene Suffer a Glomerular Mesangial Cell Defect

Abstract: bGATA3 is a zinc finger transcription factor that plays a crucial role in embryonic kidney development, while its precise functions in the adult kidney remain largely unexplored. Here, we demonstrate that GATA3 is specifically expressed in glomerular mesangial cells and plays a critical role in the maintenance of renal glomerular function. Newly generated Gata3 hypomorphic mutant mice exhibited neonatal lethality associated with severe renal hypoplasia. Normal kidney size was restored by breeding the hypomorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Of the six GATA factors, we examined the expression levels of Gata2 , Gata3 , Gata4 and Gata6 mRNAs in the kidneys and lungs compared with those in the hearts and livers. Both Gata2 and Gata3 were abundantly expressed in the kidneys, in agreement with the previous reports (Moriguchi et al., ; Yu et al., ), and also in the lungs (Figure ). Gata6 was also expressed in the lungs.…”
Section: Resultssupporting
confidence: 92%
“…Of the six GATA factors, we examined the expression levels of Gata2 , Gata3 , Gata4 and Gata6 mRNAs in the kidneys and lungs compared with those in the hearts and livers. Both Gata2 and Gata3 were abundantly expressed in the kidneys, in agreement with the previous reports (Moriguchi et al., ; Yu et al., ), and also in the lungs (Figure ). Gata6 was also expressed in the lungs.…”
Section: Resultssupporting
confidence: 92%
“…In concert with those observations, hypomorphic Gata3 g/g homozygous thymocytes were shown to exhibit a second peak of GFP fluorescence starting at the DN2 stage in thymocytes that were generated after adoptive transfer of fetal liver hematopoietic stem cells (HSC) and progenitors (see Fig. 3 in reference 49) (Gata3 g/g mutants could not be examined directly since the homozygous mutation leads to perinatal lethality [50]). In initially curious contrast, GFP fluorescence was never observed at the ETP, DN2, or DN3 stage in Gata3 g/Ï© heterozygous mutants (32,49).…”
Section: Figmentioning
confidence: 79%
“…Gata3 g (32,50), GATA3 Tg Cd2-GATA3 transgenic line 720 (36), TCR␣␀ transgenic OT-II.2 (53) (purchased from Jackson Laboratory), and TCR␀ transgenic (52) (generously provided by Karen Hathcock at National Institutes of Health, Baltimore, MD) mice were described previously and were maintained on a congenic C57BL/6J background. C57BL/6J inbred mice used for backcrossing and FVB/NJ mice were purchased from Jackson Laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 More recently, HDR has been associated with nephrotic syndrome and isolated cases of GN, 15,16 whereas Gata3 hypomorphic mutant mice rescued with a yeast artificial chromosome Gata3 transgene, whose expression was limited to renal tubules and not glomeruli, have been shown to suffer glomerular mesangial cell (MC) defects. 17 In genome-wide transcriptome studies, GATA3 has been identified as a highly enriched transcript in MCs, 18,19 but the functional significance of GATA3 expression in MCs in health and disease has not been explored. Moreover, GN in HDR could reflect the effect of GATA3 deficiency on immunity because overexpression in T cells protects against lupus nephritis in BXSB/ MpJ-Yaa mice, 20 and on ILC2s, which are reported to be central to renal repair.…”
Section: Resultsmentioning
confidence: 99%